1997
DOI: 10.1093/ndt/12.12.2521
|View full text |Cite
|
Sign up to set email alerts
|

Latin American registry of dialysis and renal transplantation: 1993 annual dialysis data report

Abstract: In spite of the economic difficulties, very important efforts have been made to treat ESRD patients and gross mortality statistics in some countries are similar to those reported by other regional registries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 1 publication
1
19
0
7
Order By: Relevance
“…In contrast, it remains uncertain whether benign nephrosclerosis (BN) consequent to essential hypertension can also cause ESRD. [1][2][3] Recent data reported by the United States Renal Data System (USRDS) 4 and by European 5 and Latin American 6 registries indicate that hypertensive nephrosclerosis (HN) is a frequent and growingly important presumed cause of ESRD among patients initiating replacement therapy. Although early epidemiological data indicated that few hypertensive patients eventually develop renal injury, 2 more recent clinical observations revealed that the relative risk of developing ESRD is increased by up to 20 times in hypertensive patients.…”
mentioning
confidence: 99%
“…In contrast, it remains uncertain whether benign nephrosclerosis (BN) consequent to essential hypertension can also cause ESRD. [1][2][3] Recent data reported by the United States Renal Data System (USRDS) 4 and by European 5 and Latin American 6 registries indicate that hypertensive nephrosclerosis (HN) is a frequent and growingly important presumed cause of ESRD among patients initiating replacement therapy. Although early epidemiological data indicated that few hypertensive patients eventually develop renal injury, 2 more recent clinical observations revealed that the relative risk of developing ESRD is increased by up to 20 times in hypertensive patients.…”
mentioning
confidence: 99%
“…This diagnosis was suspected clinically in this patient, with her strong family history of hypertension, moderate proteinuria, and no evidence of systemic disease, and confirmed by renal biopsy, as clinical observations may be misleading. [7][8][9][10] The possibility that the patient had a primary renal disease that could conceivably benefit from MMF was considered, but the demonstration of a prominent interstitial infiltrate suggested that a trial with MMF may be useful, especially as antihypertensive treatment had not altered the progressive increment in serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente, a hipertensão é a segunda maior causa de insuficiência renal crônica terminal 4,5,6 . As duas patologias podem estar ligadas principalmente de duas maneiras: a hipertensão arterial, quando em fase maligna, pode levar a quadro de nefroangiosclerose por endarterite obliterante e arteriolite necrotisante; e a forma dita "benigna" pode levar ao quadro de nefrosclerose hipertensiva e perda progressiva e lenta da função renal 7 .…”
Section: Introductionunclassified
“…Dessa forma, temos que grande parte dos pacientes em diálise chegou a esta situação tendo como causa básica a hipertensão arterial 4 . No entanto, a minoria dos hipertensos desenvolve insuficiência renal.…”
Section: Introductionunclassified